ANTAGONIST’S OBSESSION TO REVENGE IN V. E. SCHWAB’S NOVEL VICCIOUS - Cindy Karina Sunardi; Zulfan Sahri (Universitas Islam Sumatera Utara, 2022)
This paper concerns with Antagonist’s Obsession to Revenge in V. E. Swab’s novel Viccious. It refers to three points of discussion i.e. his friend’s betrayal, his friend’s injustice, and his friend’s aggressiveness. In analyzing the three points, the descriptive method is chosen as the suitable method to process the data. The analysis indicates that there are two best friends who make a research together and do the experiment on each other. Anyhow, during the experiment, many people around them die as the victims of their research experiment until finally they start to hate each other, and are obsessed to take revenge on each other. The revenge occurs when Elly’s girlfriend is found dead due to the wrong experiment conducted by Victor, and the work of injustice with aggressiveness is done to Victor by a gun shot. The results indicate that someone’s obsession on things can be a serious matter if it is wrongly conducted. The sensitive problems arises from the antagonist’s unfair ways, treating his friend so badly, and being obsessed to take killing action.